A full medical service for all : BMA's national plan
1938-04 1938 1930s 3 pages - 3 - POSITIVE HEALTH THE IDEAL Paras. 25-29 Emphasising the value of positive health measures, the report states:- "By continuous attention to such factors as housing, water and food supply, the prevention of epidemics, and the prevention and abatement of conditions injurious to health, the services administered by sanitary authorities ensure a standard of environmental circumstances which is vastly superior to anything which existed comparatively few years ago." Nutrition, overcrowding, the prevention of infectious disease, atmospheric pollution, and the provision of extensive facilities for recreation are listed as matters on which further action is needed. LOCAL GOVERNMENT CHANGES Paras.109-122 As regards local government organization the chief proposals are:- Paras.116-117 (1) Removal of public health functions from all county district councils serving a population of less than 100,000 in the case of urban areas and 75,000 for rural areas. Para. 118 (2) Establishment of a statutory committee in each public health area to which all questions relating to medical and allied services would be referred. Paras. 17 and 120 (3) Medical advisory committees in each area to maintain liaison between the local doctors and the local authority. "BEWILDERING COMPLEXITY" Paras. 20-23 Surveying the present position of the country's health services, the report states:- "The past thirty years have been characterized by a widening and a deepening of the public interest in the problems of personal and public health. The Press, the radio, and the public platform have combined to keep continually before the public as a live and personal issue 'The Health of the People'". At the same time, the report proceeds, "the existing health agencies are different in their origin and inspiration, diverse in their form, and bewildering in their complexity. The State continues steadily to increase and extend its health and sickness activities. But it cannot be said that each new development is an expression of a unified health policy of ordered development, CO-ORDINATION THE GOAL "The individual passes from local authority to voluntary body, from consulting room to clinic or hospital, from private to official doctor and often back again, to obtain from many unrelated agencies a service which could be more efficiently provided as one co-ordinated whole. Some services are available to one citizen but not to another in similar circumstances; some serve the citizen at home, while others are prohibited from so doing; some he obtains at public expense, others he must pay for privately. "What is urgently needed", the report emphasizes, "is an integrated national policy on health". With compliments from:- The Public Relations Officer, British Medical Association, Tavistock Square, W.C.1. 292/847/1/59